2008
DOI: 10.1073/pnas.0804373105
|View full text |Cite
|
Sign up to set email alerts
|

Divalent metal transporter 1 (DMT1) contributes to neurodegeneration in animal models of Parkinson's disease

Abstract: Dopaminergic cell death in the substantia nigra (SN) is central toParkinson's disease (PD), but the neurodegenerative mechanisms have not been completely elucidated. Iron accumulation in dopaminergic and glial cells in the SN of PD patients may contribute to the generation of oxidative stress, protein aggregation, and neuronal death. The mechanisms involved in iron accumulation also remain unclear. Here, we describe an increase in the expression of an isoform of the divalent metal transporter 1 (DMT1/Nramp2/ S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
329
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 369 publications
(348 citation statements)
references
References 47 publications
15
329
1
3
Order By: Relevance
“…Salazar et al [43] have shown that the ?IRE form of DMT1 is increased in the substantia nigra of Parkinson's disease patients. Given that both microcytic mice (gene symbol mk) and Belgrade rats (gene symbol b) have a G185R mutation that impairs DMT1 transport activity [10,11], they could determine whether similar increases in DMT1 were part of an inflammatory etiology of neurodegeneration in two rodent models of Parkinson's disease or were part of a protective response.…”
Section: Neural Tissue and Related Cell Typesmentioning
confidence: 99%
“…Salazar et al [43] have shown that the ?IRE form of DMT1 is increased in the substantia nigra of Parkinson's disease patients. Given that both microcytic mice (gene symbol mk) and Belgrade rats (gene symbol b) have a G185R mutation that impairs DMT1 transport activity [10,11], they could determine whether similar increases in DMT1 were part of an inflammatory etiology of neurodegeneration in two rodent models of Parkinson's disease or were part of a protective response.…”
Section: Neural Tissue and Related Cell Typesmentioning
confidence: 99%
“…Future studies could be profitably directed at testing the possibility for a two step entry process for Mn across biological membranes. It is noteworthy that when MPTP is given to mice, the expression of an isoform of DMT1 increases in the ventral mesencephalon of treated animals concomitant with iron accumulation, oxidative stress, and dopaminergic cell loss (Salazar et al 2008). Thus, DMT1 mutation impairs iron transport and protects against MPTP and 6-hydroxydopamine.…”
Section: New Considerations Regarding Mn Transportmentioning
confidence: 99%
“…At present, the aggregation mechanism of iron in the substantia nigra is not very clear, which may be related to the abnormal expression of DMT1 in brain iron regulatory proteins. DMT1 is a transmembrane iron transport protein, participating in the absorption and metabolism of iron and other metal ions in the cell with high expression of in the substantia nigra (Salazar et al 2008). The high expression of DMT1 in PD patients is the same as the abnormal aggregation of brain iron (Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 99%